2011
DOI: 10.1038/jhg.2010.170
|View full text |Cite
|
Sign up to set email alerts
|

Association of CARD8 with inflammatory bowel disease in Koreans

Abstract: Caspase recruitment domain (CARD)-containing protein 8 (CARD8) is a potential candidate risk gene for inflammatory bowel disease (IBD) because of its role as a component of the NALP3 inflammasome and as an inhibitor of nuclear factor-kappa B. Previous studies examining the association of a CARD8 single-nucleotide polymorphism (SNP) (rs2043211, p.Cys10X) with IBD yielded mixed results in Caucasians that may result from interaction with NALP3 or NOD2 (nucleotide-binding oligomerization domain 2) variants. To und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
(69 reference statements)
1
26
3
1
Order By: Relevance
“…Other authors have confirmed a role for Nlrp3 in IBD, but provided evidence that a gain-of-function mutation of Nlrp3 is associated with IBD [17,18] . Finally, two recent publications could not corroborate any genetic association between Nlrp3 and IBD [19,20] .…”
Section: Role Of the Nlrp3 Inflammasome In Ibdmentioning
confidence: 89%
“…Other authors have confirmed a role for Nlrp3 in IBD, but provided evidence that a gain-of-function mutation of Nlrp3 is associated with IBD [17,18] . Finally, two recent publications could not corroborate any genetic association between Nlrp3 and IBD [19,20] .…”
Section: Role Of the Nlrp3 Inflammasome In Ibdmentioning
confidence: 89%
“…For example, the NOD2 or ATG16L1 variants, which are regarded as firmly established CD susceptibility genes among whites, are not associated with CD in Asian populations, [1][2][3][4][5] whereas the association of the TNFSF15 variants with a CD risk is stronger in Koreans and Japanese than in whites. [6][7][8] Korean CD patients also differ from western patients in that they have a male predominance in sex distribution, 9,10 predominance of ileocolonic disease in the disease location, [9][10][11] and a higher incidence of perianal fistula in disease behavior. 10,11 Therefore, it is possible that the clinical course of CD differs between Asian and western patients.…”
mentioning
confidence: 95%
“…[6][7][8] Korean CD patients also differ from western patients in that they have a male predominance in sex distribution, 9,10 predominance of ileocolonic disease in the disease location, [9][10][11] and a higher incidence of perianal fistula in disease behavior. 10,11 Therefore, it is possible that the clinical course of CD differs between Asian and western patients.…”
mentioning
confidence: 95%
“…Ahmad-Nejad et al, 2004;Alvarez-Rodriguez et al, 2011;Brand et al, 2005;Britton et al, 2001;Coenen et al, 2010;Feldmann et al, 2002;Gazouli et al, 2005;Hoffman et al, 2001Hoffman et al, , 2003Neven et al, 2004;Pontillo et al, 2011;Schoultz et al, 2009;Shen et al, 2010;Snelgrove et al, 2007;Villani et al, 2009;Yang et al, 2011)…”
unclassified